2014
DOI: 10.1371/journal.pone.0086211
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Profiling of the Tissue-Specific Expression of Genes Related with Insulin Sensitivity in Dairy Cows during Lactation Focusing on Different Fat Depots

Abstract: In dairy cows the milk associated energy output in early lactation exceeds the input via voluntary feed intake. To spare glucose for mammary lactose synthesis, peripheral insulin sensitivity (IS) is reduced and fat mobilization is stimulated. For these processes a link between IS and the endocrine functions of adipose tissue (AT) is likely; we thus aimed to characterise the mRNA expression from bovine AT derived proteins and receptors that are related to IS according to the literature in metabolically active t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 95 publications
(138 reference statements)
10
45
1
Order By: Relevance
“…The lack of changes in the expression of ADIPOQ and its receptors from pregnancy to early lactation was consistent with previous studies (Giesy et al, 2012;Selim et al, 2014). Conversely, Ji et al (2012), Khan et al (2013), and Saremi et al (2014) reported that the expression of ADIPOQ gradually decreased during the peripartal period. However, Giesy et al (2012) reported that plasma ADIPOQ concentrations may decrease during early lactation independently of ADIPOQ expression in SAT, and indicated that the formation of circulating ADIPOQ complexes may be a major determinant of the plasma concentrations of this adipokine.…”
Section: Effect Of Overfeeding On Sat Gene Expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…The lack of changes in the expression of ADIPOQ and its receptors from pregnancy to early lactation was consistent with previous studies (Giesy et al, 2012;Selim et al, 2014). Conversely, Ji et al (2012), Khan et al (2013), and Saremi et al (2014) reported that the expression of ADIPOQ gradually decreased during the peripartal period. However, Giesy et al (2012) reported that plasma ADIPOQ concentrations may decrease during early lactation independently of ADIPOQ expression in SAT, and indicated that the formation of circulating ADIPOQ complexes may be a major determinant of the plasma concentrations of this adipokine.…”
Section: Effect Of Overfeeding On Sat Gene Expressionsupporting
confidence: 91%
“…The decline of LEP during the transition period concurred with previous studies showing a decrease of plasma LEP concentration (Block et al, 2001;Kokkonen et al, 2005) or LEP expression (Saremi et al, 2014;Selim et al, 2014). The downregulation of LEP postpartum in both groups and particularly in the HE group may support the concomitant retrieval of DMI and energy balance (Roche et al, 2013).…”
Section: Effect Of Overfeeding On Sat Gene Expressionsupporting
confidence: 89%
See 2 more Smart Citations
“…To date, no measurements of neurotrophic factors and their receptor in adipose tissues of cattle have been reported, but it is well known that fat depot mass and biological activity changes dramatically during the lactation cycle in dairy cows (Saremi et al, 2014). Similarly, a large body of research has been devoted to the study of fat metabolism and its implication on physiological regulation during health and disease conditions in dairy cows (McNamara and Hillers, 1986;Graugnard et al, 2012 andSgorlon et al, 2015).…”
mentioning
confidence: 99%